Dni Nauki i Techniki Radzieckiej. (Gdańsk : NOT, 1987)
Afisz informujący o wystawie 30.09.1987 r. w gdańskim NOT.
Keywords: Gdańsk (Polska) -- 1945-1990 -- druki ulotne; Gdańsk (Polska) -- 1945-1990 -- źródła; Gdańsk (Polska) -- 1945-1990 -- życie intelektualne